Utilization of Steel Slag as Partial Replacement of Fine Aggregate Material in Concrete (International Journal of Scientific Research in Science and Technology, 2024)
Concrete is the most used building material in the world. As a sustainable approach in this project explores the potential benefits of incorporating steel slag sand in concrete mixtures. The objective is to study the mineralogical properties of cement, steel slag to study the strength parameter like compressive strength at 7, 14, 28 days for all mix proportions. This project investigates the utilization of the replacement of fine aggregate with steel slag sand in concrete mixes. The study evaluates the impact of these components on the mechanical properties of concrete through compression tests conducted over varying time intervals. Results indicate that as the proportion of steel slag sand increase, there is a corresponding enhancement in compressive strengths of the concrete mixes. Mix 5, containing the highest proportions of these components with 50% M- Sand and Steel slag sand, consistently demonstrates superior mechanical properties compared to other mixes, showcasing an impressive increase in compressive strengths. This highlights the effectiveness of finer particle sizes and improved packing density.